Walter Benjamin's other history : of stones, animals, human beings, and angels - Hanssen, Beatrice (University of California Press, 1998)
In this study, Beatrice Hanssen unlocks the philosophical and ethical dimensions of the Trauerspiel study, showing how its thematics persisted well into the later writings of the thirties. For by introducing the materialistic category of natural history in The Origin of German Tragic Drama, Benjamin not only criticized idealistic conceptions of history writing but also expressed an ethico-theological call for another kind of history, one no longer anthropocentric in nature. This profound critique of historical thinking, Hanssen shows, went hand in hand with a radical de-limitation of the human subject, informed by his interest in questions about ethics, the law, and justice. Through an analysis of the seemingly innocuous figures of stones, animals, and angels that are scattered throughout his writings, Hanssen reconstructs the often neglected ethical dimension of his historical thought. In the course of doing so, she not only places Benjamin's work in the context of contemporaries such as Adorno, Cohen, Lukacs, Kafka, Kraus, and Heidegger but also demonstrates the persistence of Benjaminian themes in contemporary philosophy and critical theory.
Keywords: Benjamin, Walter, -- 1892-1940 -- Philosophy.; Benjamin, Walter, -- 1892-1940; LITERARY CRITICISM -- European -- German.; Philosophy; Sociale filosofie.; Cultuurfilosofie.; Tragedies.